2020
DOI: 10.1186/s42522-020-00016-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of WGS-subtyping methods for epidemiological surveillance of foodborne salmonellosis

Abstract: Background: Salmonellosis is one of the most common foodborne diseases worldwide. Although human infection by non-typhoidal Salmonella (NTS) enterica subspecies enterica is associated primarily with a self-limiting diarrhoeal illness, invasive bacterial infections (such as septicaemia, bacteraemia and meningitis) were also reported. Human outbreaks of NTS were reported in several countries all over the world including developing as well as high-income countries. Conventional laboratory methods such as pulsed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the same vein, the phylogenetic tree obtained from SNPs exhibited diverse clustering of the isolates with an initial one singleton and two clades that subsequently bifurcated. Phylogenetic analysis based on WGS-derived has proven to be a superior cluster resolution method compared to many of the standard subtyping methods (Mohammed and Thapa, 2020;Ford et al, 2021). In order to determine the genetic relatedness among the isolates and infer their evolutionary history based on a genome-wide scale, across the genomes of all S. Enteritidis and closely related serovars were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, the phylogenetic tree obtained from SNPs exhibited diverse clustering of the isolates with an initial one singleton and two clades that subsequently bifurcated. Phylogenetic analysis based on WGS-derived has proven to be a superior cluster resolution method compared to many of the standard subtyping methods (Mohammed and Thapa, 2020;Ford et al, 2021). In order to determine the genetic relatedness among the isolates and infer their evolutionary history based on a genome-wide scale, across the genomes of all S. Enteritidis and closely related serovars were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Zoonotic S. Typhimurium DT104, as well as DT104b, has a broad-host-range, and it is primarily transmitted through food sources and the faecal-oral route. The infection ranges from self-limiting gastroenteritis to invasive disease that requires prompt antibiotic therapy [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Non-typhoidal Salmonella (NTS) serovars predominantly cause a self-limiting diarrhoeal illness; however, they have recently observed to cause invasive extra-intestinal disease, including bacteraemia and focal systemic infections [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that SNP and genomic MLST results are congruent and both approaches can analyze the outbreaks of foodborne illnesses [49]. However, a recent study that investigated two outbreaks using different WGS subtyping methods revealed that SNP-based analyses have the ability to confirm the occurrence of the outbreak while both cgMLST and wgMLST could neither differentiate outbreak-related Salmonella Typhimurium isolates from outbreak-unrelated isolates nor confirm the source of infection [50]. Consequently, WGS based on SNP was selected for further investigation.…”
Section: Discussionmentioning
confidence: 99%